1990
DOI: 10.1128/mcb.10.6.3003
|View full text |Cite
|
Sign up to set email alerts
|

Antigen receptor-induced cell cycle arrest in WEHI-231 B lymphoma cells depends on the duration of signaling before the G1 phase restriction point.

Abstract: The murine B lymphoma cell line WEHI-231 has been extensively used to study antigen receptor regulation of B-cell growth (11,14,15,20,23,31

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…2D). It was previously reported that BCR crosslinking induced G 0 /G 1 arrest of WEHI-231 cells before the induction of apoptosis (10,11). Anti-IgM stimulation induced a similar level of G 0 /G 1 arrest in transfectants with WT and S62A mutant Bcl-xL (Supplemental Fig.…”
Section: Phosphorylation Of Ser 62 Of Bcl-xl Is Important For Its Ubimentioning
confidence: 63%
See 1 more Smart Citation
“…2D). It was previously reported that BCR crosslinking induced G 0 /G 1 arrest of WEHI-231 cells before the induction of apoptosis (10,11). Anti-IgM stimulation induced a similar level of G 0 /G 1 arrest in transfectants with WT and S62A mutant Bcl-xL (Supplemental Fig.…”
Section: Phosphorylation Of Ser 62 Of Bcl-xl Is Important For Its Ubimentioning
confidence: 63%
“…We studied the apoptosis-induction system of WEHI-231 cells that undergo growth arrest and apoptosis following crosslinking of IgM on the cell surface, which mimics the deletion of self-reactive B cells in the bone marrow (8)(9)(10)(11). Anti-IgM stimulation induces cell death in 12-24 h. WEHI-231 cells were cultured in the presence of 10 mg/ml of anti-IgM, and expression of the antiapoptotic factor Bcl-xL was assessed by Western blot.…”
Section: Bcr Crosslinking In Wehi-231 Cells Induces Bcl-xl Degradatiomentioning
confidence: 99%
“…Cross-linking of membrane IgM on WEHI-231 cells results in growth arrest and the induction of apoptosis (31)(32)(33). Because of this functional response, WEHI-231 cells have been used extensively as a model for immature B cell negative selection.…”
Section: Hsh2 Protects Wehi-231 Cells From Undergoing Bcr-induced Apomentioning
confidence: 99%
“…On the other hand, the ectopic expression of cyclin A and E, the activating partners of Cdk2, can overcome pRbmediated growth arrest in G1 by inducing pRb hyperphosphorylation (Hinds et al, 1992). Because anti-IgM prevents phosphorylation of pRb in WEHI-231 cells only when added in early G1 (Joseph et al, 1995), and leads to growth arrest near the G1/S border without affecting the duration of G1 (Page and DeFranco, 1990), we set out to determine whether negative signaling affects the accumulation and activity of cyclin A or cyclin E-associated kinase complexes. Although cyclin A proteins were easily detected in lysates of WEHI-231 cells by immunoblotting and immunoprecipitation, the level of cyclin E expression was very low even in exponentially growing cells, as reported recently for murine splenic B-cells (Tanguay and Chiles, 1994).…”
Section: Introductionmentioning
confidence: 99%